Предмет: Алгебра, автор: sergm021

Помогите решить 22 д

Приложения:

Ответы

Автор ответа: eugeke
0
 frac{a^{-2}+b^{-2}}{a^{-1}+b^{-1}}cdot( frac{a^2+b^2}{ab})^{-1}-(a+b)^{-1}= frac{ (frac{1}{a})^2 +( frac{1}{b})^2}{ frac{1}{a}+ frac{1}{b}}cdot frac{ab}{a^2+b^2}- frac{1}{a+b}=\\
=  frac{ frac{a^2+b^2}{a^2b^2}}{ frac{a+b}{ab}}cdot frac{ab}{a^2+b^2}- frac{1}{ab}= frac{a^2+b^2}{a^2b^2}cdot frac{ab}{a+b}cdot frac{ab}{a^2+b^2} - frac{1}{a+b}= \\
= frac{1}{a+b}- frac{1}{a+b}=0
Похожие вопросы
Предмет: Другие предметы, автор: horosaadevocka725